Comparison of tunnel ligament release instrument assisted minimally open surgery and conventional open surgery in the treatment of tarsal tunnel syndrome - Gültaç, E.; Kılınç, B.; Kılınç, C. Y.; Yücens, Mehmet; Aydogan, N. H.; Öznur, A. (SAGE Publications, 2020)
Aim: This study compared the results of tarsal tunnel syndrome release surgeries using mini-open incisions and standard incisions. Patients and Methods: From January 2012 until April 2018, 31 feet of 29 patients diagnosed with tarsal tunnel syndrome were treated surgically. 15 feet of 15 patients underwent surgeries utilizing minimally open technique and 16 feet of 14 patients underwent surgeries utilizing standard incisions. The following preoperative and postoperative data was obtained: foot and ankle muscle testing results, posture analyses, anthropometric measurements, joint movement ranges, pain complaints, endurance evaluation results, and functional test results. The mean follow-up period was 38 months (13–88 months). Results: The mean operation times were 26.8 min (23–30 min) using the standard incision and 13.3 min (9–17 min) using the mini-open incision (p < 0.05). In the preoperative and postoperative comparisons of the total muscle strength and total joint limit values of the healthy and affected feet, statistically significant improvements were observed in both the mini-open incision and standard incision groups (p < 0.05). Moreover, statistically significant improvements were seen in both groups in the postoperative repeated toe raises for 1 minute assessments of the affected foot (p < 0.05). In the foot function index and functional foot score values, statistically significant improvements were seen between the preoperative and postoperative values in both groups (p < 0.05). Conclusions: Based on the results of this study, using a tunnel ligament release instrument assisted minimally open surgery to loosen the laciniate ligament may present an alternative to the standard incision, with its significantly decreased morbidity rate and cosmetic success.
Keywords: Decompression; Adult; Male; decompression; release; Young Adult; instrument; Humans; Minimally Invasive Surgical Procedures; Orthopedic Procedures; Postoperative Period; Mini-open; Aged; Orthopedic surgery; Instrument; Tarsal tunnel; tarsal tunnel; Middle Aged; Decompression, Surgical; mini-open; Treatment Outcome; Release; Female; short incision; RD701-811; Ankle Joint; Tarsal Tunnel Syndrome; 2. Zero hunger